Pembiasaan Rajin Menabung dan Kegiatan Jum’at Beramal pada Siswa Kelas IV SD Negeri Kalikalong 01 Kabupaten Pati - Sukma, Youvani Laila (Pena Edukasia, 2022)
This study aims to find out how the implementation of saving activities and Friday charity activities for fourth graders at Kalikalong 01 State Elementary School, Pati Regency. The background that drives this research is the importance of habituation of saving and charitable activities for students from an early age. This is important because through this habituation will shape the personality and character of students who are good in the future and instill the behavior of saving life and helping each other to others. This type of research is a qualitative research with data collection techniques in the from of questionnaires and documentation. The subjects of this study were fourth grade students. From the results of research on saving activities based on the results of the questionnaire, it can be concluded that if students think about their future needs, they can still be managed if they are interested in saving their money at school. Then the results of research on Friday charity activities that most students are active in participating in these activities. This activity is able to train students to care for each other and help others who are experiencing difficulties, and it can be seen that student solidarity is starting to develop, because most students have started consistently showing their various participations in the implementation of Charity Friday activities.